Complicaciones en el recién nacido prematuro y su relación con la mortalidad neonatal en el Servicio de Neonatología del Hospital General Isidro Ayora de Loja periodo enero-junio 2016. - Jaramillo Mendoza, Jhonny Alejandro (2017)
A premature newborn is one who is born before the 37th week of gestation. The majority of neonatal deaths occur in preterm infants because they combine a number of factors that make their vulnerability closely linked to immaturity increase and the risk of complications is high. The present investigation is descriptive, prospective, qualitative and cross-sectional, and is aimed at "Identifying complications in the preterm newborn and its relation with neonatal mortality in the Neonatology Service of General Hospital Isidro Ayora" de Loja. "The study included 67 critically ill preterm infants, the most common complication being hyperbilirubinemia with 23.95 %% followed by conduction hearing loss and retinopathy of prematurity with 14.97%, necrotizing enterocolitis with 13.17% These complications occur more in the male gender with 56.61% and there is a mortality associated with complications in a percentage of 4.47%. Keywords: Premature, Hyperbilirubinemia, hearing loss, retinopathy, mortality